Virtual Synchronous Machine Control for Doubly Fed Induction Machine-Based Wind Energy Conversion Systems - ANDRE THOMMESSEN; Christoph Michael Hackl (IEEE Open Journal of the Industrial Electronics Society)
Renewable inverter-based resources (IBRs), such as wind energy conversion systems (WSs), replace directly grid-connected synchronous machines (SMs). Standard grid-following (GFL) control of IBRs decreases the power system inertia. This article proposes virtual synchronous machine (VSM)-based grid-forming (GFM) control for doubly fed induction machine (DFIM)-based WSs with the following extensions: feedforward torque control (FTC) for maximum power point tracking (MPPT), MPPT compensation for accurate inertia emulation, reference power point tracking to provide energy reserves, dynamic droop saturation control to mitigate power overloading, and grid voltage control utilizing DFIM stator and rotor-side back-to-back inverter reactive power. The WSs are integrated into the IEEE 9-bus test system. Comprehensive simulation results give insights into (V)SM-based power system dynamics. Compared with existing VSM control without FTC, the proposed FTC increases the wind energy yield, i.e., typical MPPT performance is achieved, similar to GFL control. For high power penetration of IBRs, the proposed VSM control enables stable operation due to its GFM capability, whereas GFL control tends to instability. The VSM provides higher power system damping than a real SM due to adaptable internal damping. If wind power reserves are available, the fast VSM droop control provides additional damping by adapting the virtual turbine power without the dominant delays of real turbine dynamics.